THE EFFECTIVENESS OF THE METHODS OF USING HUMIC STIMULATORS IN THE TECHNOLOGY OF WINTER WHEAT CULTIVATION - Marenych, M. M. (Scientific Progress & Innovations, 2019)
The results of the economic efficiency of the methods of using humic stimulators as an element of winter wheat yield management are presented. Using humic stimulators in the mixture with disinfectants led to in-creasing yields and economic indices in the majority of variants. The analysis of the economic indices of us-ing humates proves their efficiency in pre-sowing treatment of wheat seeds. Variety properties also indisput-ably influence economic indicators. In our experiment Smuhlianka variety turned out to be better adapted to cultivation conditions and gave higher yields and profitability of production – 117 versus 98.3 %. The yield increase as a result of using Maxym Star 025 FS disinfectant made 3.3 metric centners per hectare on the average for all the varieties, net profit was 1552 hryvnias higher as compared with the control.Using Ra-dostym turned out to be less economically efficient, however, however, it was positive in comparison with the control. The variants, in which 1R Seed treatment (1.0 l/t) was used, were the most efficient. In case of using only this preparation the yield increase made almost 6 metric centners per hectare in comparison with the control variant, and the yield increase while its using together with disinfectant was 6.3 metric centners per hectare. Thus, despite the considerable price of 1R Seed treatment, in the given dose it is the best prepara-tion for pre-sowing treatment of wheat seeds both in the complex with disinfectant and without it: the net profit as a result of using this preparation made 2480 hryvnias. Soil fertility activator 5R Soil Boost used in the amount of 11 kg/ha resulted in increasing wheat grain yield by 4.8 metric centners per hectare, however, in fact, the high enough price of the preparation levels its advantages for receiving net profit – it was almost the same as in the control variant, and profitability index was even 8.3 % lower. The highest economic effi-ciency was registered in the variant, in which only foliar application of 4R Foliar concentrate was used twice: 2 kg/ha in each case. The highest economic efficiency of using humates mixed with herbicides was observed in the variant in which the mixture of Prima (400 g/ha) and Foliar concentrate (2 kg/ha) was used. Adding 200 g/ha of Humifield to the herbicide solution resulted in the yield increase, and combining the mix-ture with Foliar concentrate (2 kg/ha) increased the yield by 6.4 metric centners per hectare. Correspond-ingly, the indices of the net profit were 2816 hryvnias and profitability – 15.5 % higher.